ASSESSING THE IMPACT OF AUTHENTIC KOREAN MEDIA ON STUDENTS’ LINGUOCULTURAL COMPETENCE - Pulatova Dilrabo Dilshodovna (Modern American Journals, 2025)
This article explores the impact of authentic Korean media on the development of linguocultural competence among students majoring in Korean language. Linguocultural competence, which bridges linguistic accuracy and cultural understanding, is critical for effective communication and intercultural awareness. Authentic media including K-dramas, news broadcasts, YouTube vlogs, and social media provide learners with exposure to real-life language use, pragmatic norms, sociocultural references, and everyday communication styles in Korean. Through a quasi-experimental study involving 60 undergraduate students, the research compares traditional classroom instruction with media-enhanced learning. Findings indicate that students exposed to authentic media demonstrated significantly greater improvements in recognizing honorifics, idiomatic expressions, and culturally rooted gestures. Furthermore, learners reported increased motivation, deeper cultural empathy, and enhanced ability to interpret implicit cultural meanings. The study emphasizes the pedagogical value of integrating media into language curricula and suggests strategies for guided media consumption to maximize learning outcomes. The article concludes by recommending criteria for selecting appropriate media and assessment tools for evaluating linguocultural growth in Korean language learners.
Keywords: Korean language, linguocultural competence, authentic media, K-dramas, language learning, pragmatics, cultural immersion.